Cover Image, Volume 173A, Number 7, July 2017. Issue 7 (July 2017) - Kalish, Jennifer M.; Biesecker, Leslie G.; Brioude, Frederic; Deardorff, Matthew A.; Di Cesare‐Merlone, Alessandra; Druley, Todd; Ferrero, Giovanni B.; Lapunzina, Pablo; Larizza, Lidia; Maas, Saskia; Macchiaiolo, Marina; Maher, Eamonn R.; et al.
Abstract : The cover image, by Jennifer M. Kalish et al., is based on the Original Article Nomenclature and definition in asymmetric regional body overgrowth, DOI:10.1002/ajmg.a.38266 .